Wallowing in Buffaloes: An Overview of its Impact on Behaviour, Performance, Health and Welfare (Indian Journal of Animal Production and Management, 2024)
Understanding the pivotal role of wallowing in  water buffaloes is imperative in designing  appropriate housing systems that cater to their  species-specific behaviours and innate  requirements. Wallowing, a behaviour allowing  buffaloes to cope with high levels of heat and  humidity facilitates evaporative heat loss, serving  as their primary mechanism for heat regulation.  This is particularly crucial due to their limited sweat  glands and heat-absorbing black skin. However, the  shift from extensive to intensive husbandry  practices has curtailed wallowing opportunities for  buffaloes, potentially jeopardizing their well-being.  This review underscores the significance of  wallowing for water buffaloes and its profound  effects on their thermoregulation, behaviour,  productivity, reproductive responses, and health  considerations. Additionally, it delves into the  motivations and challenges associated with  providing wallowing opportunities in intensive  husbandry systems.
Keywords: behaviour; buffalo; heat stress; wallowing and welfare